A Hidden Curriculum Practices: at Avicenna Senior High School - Atik Kurniawati (Program Studi Manajemen Pendidikan, 2019)
This paper departs from the issue of a hidden curriculum that occurred during the last 10 years. Hidden curriculum is an educational practice in schools that contributes to the progress of education. Previous studies discussed the role of the state, the role of schools and the role of teachers in the practice of hidden curriculum separately. Whereas in this paper, researchers want to show the practice of hidden curriculum comprehensively. This research is a case study research with a qualitative approach. Findings in this study (1) Stakeholders influence the progress of schools with innovation and creation through cooperation, adaptive policies and implementation in learning activities. (2) The practice of hidden curriculum is carried out in academic and non-academic activities, but there is a dynamic that occurs in the practice of hidden curriculum (3) The achievement in the practice of hidden curriculum is seen formally and substantively. This research suggests that it is necessary to increase trust between stakeholders to be able to work together to achieve maximum achievement